Pengaruh Beban Kerja, Disiplin Kerja dan Stres Kerja terhadap Kinera Karyawan pada PT Hindoli (A Cargill Company) - Dika Apriyani; Endah Dewi Purnamasari; Try Wulandari (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine how much influence the level of workload, work discipline, and work stress on employee performance at PT Hindoli (A Cargill Company). This study uses quantitative methods and analysis using multiple linear regression analysis. Testing this research using SPSS version 24 with a total sample of 93 respondents. The results of the first regression analysis prove that workload (X1) has no effect on employee performance, which means that H1 is rejected. The level of tasks given by the company is in accordance with the abilities of employees, and the majority of employees are men who have stronger immune systems so that the workload does not affect employee performance. The results of the second regression analysis prove that work discipline (X2) has an effect on employee performance, which means that H2 is accepted. The higher the level of work discipline, the better the employee's performance. The results of the third regression analysis prove that work stress (X3) affects employee performance, which means H3 is accepted. The stress experienced by employees is low stress that employees can still overcome and it does not become an obstacle to employee performance. Taken together, the variables of workload (X1), work discipline (X2) and work stress (X3) affect employee performance.